Pathogenesis of periodontitis - A potential role for epithelial-mesenchymal transition - Saif S. Saliem; Salwan Y. Bede; Paul R. Cooper; Ali A. Abdulkareem; Michael R. Milward; Bashar H. Abdullah (Elsevier, 2022)
Epithelial mesenchymal transition (EMT) is a process comprising cellular and molecular events which result in cells shifting from an epithelial to a mesenchymal phenotype. Periodontitis is a destructive chronic disease of the periodontium initiated in response to a dysbiotic microbiome, and dominated by Gram-negative bacteria in the subgingival niches accompanied by an aberrant immune response in susceptible subjects. Both EMT and periodontitis share common risk factors and drivers, including Gram-negative bacteria, excess inflammatory cytokine production, smoking, oxidative stress and diabetes mellitus. In addition, periodontitis is characterized by down-regulation of key epithelial markers such as E-cadherin together with up-regulation of transcriptional factors and mesenchymal proteins, including Snail1, vimentin and N-cadherin, which also occur in the EMT program. Clinically, these phenotypic changes may be reflected by increases in microulceration of the pocket epithelial lining, granulation tissue formation, and fibrosis. Both in vitro and in vivo data now support the potential involvement of EMT as a pathogenic mechanism in periodontal diseases which may facilitate bacterial invasion into the underlying gingival tissues and propagation of inflammation. This review surveys the available literature and provides evidence linking EMT to periodontitis pathogenesis.